Pregnancy Risk, Contraception and Sexually Transmitted Infections in the Transgender Patient [4F]. (May 2017) - Jasani, Sona; Balica, Adrian; Marshall, Ian; Ayers, Charletta; Bachmann, Gloria; Francis, Amanda
Abstract : INTRODUCTION: Reproductive risk assessment, STI prevention and contraception counseling represent an emerging challenge in the transgender population. Despite increased awareness of transgender healthcare needs, provider templates of care based on evidence based data that address the reproductive healthcare needs of transgender individuals are limited. METHODS: We performed a literature search using Pub Med, Scopus and Google Scholar between 2010-2016. Search terms used included transgender, pregnancy, contraception, and STI. Of the six relevant articles, three were cross sectional surveys and three were retrospective cohort studies. RESULTS: Among transgender youth, contraception use did not differ between those at risk for pregnancy vs those not at risk. As expected, sexual activity was associated with higher STI risk. Positive HIV status did not differ in transmen compared to transwomen: overall HIV prevalence was higher in the trans vs non-trans population. Unprotected sex may be a factor with STI. In one study, 88% of transmen reported using no protection. Further, pregnancy appears to be desired in select transmen, as one study noted that 68% in their cohort had a planned gestation while 32% had an unplanned one. CONCLUSION: There are limited data to formulate guidelines regarding pregnancy, STI counseling and contraceptive management of transgender individuals. Both pregnancy risk/desire exists in this population and should be a counseling topic. In addition, contraceptive and STI counseling is essential during all clinical encounters. For those at risk for HPV coinfection continued gynecological surveillance should be part of their preventive health management.